Navigating the Path to Recovery: A Scoping Review of Return to Work Program for Manufacture Workers After Occupational Injury - Kurnianto, Arie Arizandi; Zsolt, Nemeskéri; Ágoston, István (Universitas Airlangga, 2023)
Introduction: Workplace accidents in the manufacturing industry may significantly affect both a worker's capacity to return to work and their general well-being. Effective return-to-work programs may help disabled workers rehabilitate. The present scoping review endeavors to scrutinize the extant body of literature pertaining to Return to Work programs tailored specifically for individuals employed in the manufacturing industry who have experienced occupational injuries. Methods: A comprehensive exploration was conducted across various scholarly databases, including PubMed, Scopus, and Web of Science. The search technique includes return-to-work, occupational injury, and manufacturing keywords. Inclusion criteria were used to screen studies. Results: A total of 5 studies were included in the final analysis, representing a range of program types, implementation strategies, and evaluation methods. The results of this review suggest that return-to-work programs can be effective in facilitating workers' return to work after occupational injury and promoting positive health outcomes. Key program components identified as contributing to program effectiveness included workplace accommodations, early return-to-work programs, and rehabilitation services. Conclusion: This scoping review emphasizes the necessity of return-to-work programs for wounded manufacturing employees. The findings of this comprehensive review indicate that return-to-work programs when meticulously crafted and effectively executed, possess the capacity to assume a pivotal function in facilitating the reintegration of injured workers into the workforce, while concurrently enhancing their holistic health outcomes. Additional investigation is warranted to enhance comprehension of the precise constituents of a program that contribute to its triumph and to delve into the efficacy of diverse implementation methodologies.